HUKUM DAN HAK PASIEN DALAM MENDAPATKAN PELAYANAN KESEHATAN DI ERA PANDEMIK - DWI UTORO (HUKUM PEMBANGUNAN EKONOMI, 2021)
The whole world community agrees that the right to health is a basic right (Fundamental Right) that is owned by every human being. The right to health which was previously seen as merely a private matter related to the fate or gift of God, has now undergone a very large paradigm shift into a legal right (legal rights) which is certainly guaranteed by the state. In the midst of the Covid-19 pandemic that has spread to almost all regions of Indonesia, the Government must be prepared to issue various strategic policies so that it can carry out its obligations to always guarantee the fulfillment of the right to health for all people. This research uses the method of library research with the statutory approach. This research found that the Government's policy to determine the Public Health Emergency status and choosing Large-Scale Social Restrictions as an option to respond to Public Health Emergency is a wise step, besides the Government must also pay attention to the economic and fiscal sectors according to the conditions and capabilities of the country.Keywords: Right to health, health service, Pandemic Covid-19. Di tengah pandemi Covid-19 yang telah menyebar hampir ke seluruh wilayah Indonesia, Pemerintah harus sigap mengeluarkan berbagai kebijakan strategis agar dapat menjalankan kewajibannya untuk senantiasa menjamin terpenuhinya hak atas kesehatan bagi seluruh masyarakat. Penelitian ini menggunakan metode penelitian kepustakaan dengan pendekatan peraturan perundang-undangan. Penelitian ini menemukan bahwa Pemerintah terlalu lamban mengambil tindakan antisipatif maupun mitigasi dalam menanggulangi pandemi corona. Pada akhirnya Pemerintah menetapkan status Darurat Kesehatan Masyarakat dan memilih Pembatasan Sosial Berskala Besar sebagai opsi untuk merespons Kedaruratan Kesehatan Masyarakat, disamping Pemerintah juga tetap harus memperhatikan sektor ekonomi dan fiskal sesuai kondisi dan kemampuan negara.Kata Kunci: Hak Pasien, Pelayanan Kesehatan, Pandemi Covid-19.